KARAKTER TOKOH UTAMA DALAM NOVEL SALAH ASUHAN KARYA ABDOEL MOEIS - Alya Amelia; Dwita Intan Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the character of the main character in the novel Salah Asuhan by Abdoel Moeis. This novel depicts the inner and social conflicts experienced by the character Hanafi, a native who is influenced by Western culture, as well as his tragic relationship with Corrie du Bussee, an Indo-Dutch woman. This study uses a qualitative descriptive method with a literary psychology approach. Data were obtained through an in-depth reading of the novel text and analyzed based on character and characterization theories. The results show that the main character, Hanafi, has a complex character characterized by ambition, low self-esteem, stubbornness, and being torn between traditional values ​​and Western modernity. This character is a reflection of the clash of colonial cultures that occurred during the Dutch colonial period. In addition, Abdoel Moeis through the character of Hanafi wants to convey criticism of the attitude of society that loses its identity due to the influence of foreign culture. This study is expected to provide a deeper understanding of the depiction of characters in classical Indonesian literature and become teaching materials in literature learning in secondary schools.